Decitabine Treatment Could Ameliorate Primary Iron-Overload in Myelodysplastic Syndrome Patients. (21st April 2015) - Shucheng, Gu; Chunkang, Chang; Youshan, Zhao; Juan, Guo; Chengming, Fei; Xi, Zhang; Chao, Xiao; Xiao, Li
<x xml:space="preserve">Abstract</x> In order to research how does hypomethylating agents ameliorate iron metabolism in myelodysplastic syndrome (MDS), we performed methylation-specific, polymerase chain reaction (MSP), bisulfate genomic sequencing polymerase chain reaction (BSP), quantitative real-time PCR and western blot of hemojuvelin (HJV) and ELISA assay for hepcidin before and after demethylating therapy (decitabine) to determine whether the change of HJV methylation status would have an influence on hepcidin expression. Eleven of 22 MDS patients achieved CR or PR according to IWG criteria (50%). HJV mRNA was induced in decitabine responders (p = .006 comparing pre/post decitabine treatment) but not in non-responders (p = .121). Similarly, hepcidin serum expression increased from 320.77 ± 34.8 μg/L to 366.77 ± 21.90 μg/L (p = .012) in responders but did not significantly change in non-responders (p = .058), while no difference of adjusted serum ferritin (ASF) was found. In conclusion, hypermethylation of HJV promoter region could silence the gene expression and demethylating therapy might ameliorate iron-overload through HJV demethylation.